Harmonic analysis of surface instability patterns on colloidal particles - Kämäräinen, Tero; Ago, Mariko; Seitsonen, Jani; Raula, Janne; Kauppinen, Esko I.; Ruokolainen, Janne; Rojas, Orlando J. (Soft Matter, 2018)
Wrinkling of colloidal particles alter a wide variety of interfacial properties but quantitative topographical descriptions have been explored experimentally to a very limited extent. In this study, we present a harmonic analysis of surface wrinkles and folds on submicron colloidal particles, obtained using an aerosol flow route, with small radius (<300 nm) and high crust thickness-to-radius ratio (>0.1). The particle surface coordinates were mapped in their entirety using cryo-electron tomography and subsequently reconstructed using spherical harmonics, allowing a spectral topographical description of the instability patterns and the identification of their surface modes by lateral wavelength. Wrinkled and crumpled particles showed a similar surface roughness spectrum, wherein differences were found most noticeable in the large wavelength region. The analysis of preferred directions of harmonic frequencies indicated a possible axial or planar alignment attributed to the directionality of the surface corrugations. The employed characterization methodology can further the study of topographical influences on colloidal interactions.
Created from Fastlane, Scopus look-up